A bioinspired heterogeneous catalyst based on the model of the manganese-dependent dioxygenase for selective oxidation using dioxygen. Issue 28 (20th March 2017) - Chaignon, Jérémy; Gourgues, Marie; Khrouz, Lhoussain; Moliner, Nicolás; Bonneviot, Laurent; Fache, Fabienne; Castro, Isabel; Albela, Belén
Abstract : A hybrid bioinspired material with manganese(ii ) complexes grafted on the surface of a mesostructured porous silica is investigated. Abstract : A hybrid bioinspired material with manganese(ii ) complexes grafted on the surface of a mesostructured porous silica is investigated. The Mn sites mimic the manganese-dependent dioxygenase (MndD), which is an enzyme that catalyses the oxidation of catechol derivatives. The metal complexes were introduced in the silica using a dinuclear complex [Mn2 L2 (Cl)2 (μ-Cl)2 ] as a precursor with a clickable ligand N, N ′-bis[(pyridin-2-yl)methyl]prop-2-yn-1-amine (L ). Azide moieties covalently grafted on MCM-41 type mesoporous silica were utilised to anchor the manganese complex through Huisgen cycloaddition using CuBr(PPh3 )3 as a catalyst. A second functional group – trimethylsilyl or pyridine—was grafted on the silica to bring, together with nanopore size confinement, a similar metal environment as in MndD. The mesostructure of the materials was maintained after incorporation of the Mn complex. Catalytic oxidation of 3, 5-di- t -butyl-catechol (3, 5-DTBC) into quinone occurred without the need of an additional base when the metal complex was confined in the porous solid. In comparision, the oxidation of 4- t -butyl-catechol (4-TBC) that always required a basic media led to a total oxidation into the ortho -quinone, contrary to the molecular analogue.